PENINGKATAN KAPASITAS PENGURUS DALAM PENGELOLAAN ADMINISTRASI PONDOK PESANTREN API SYUBBANUL WATHON METESEH - Sekar Meika Chandra; Siswanto (Institut Agama Islam Syubbanul Wathon Magelang, 2021)
This service aims to increase the capacity of the board in managing the administration of the cottage. Increasing the capacity of administrators in the administration of Islamic boarding schools is very necessary so that administrative or administrative activities of Islamic boarding schools run well and smoothly. An admin is closely related to correspondence, recording, compiling, and entering data, bookkeeping, setting the agenda and other technical matters to support organizational goals. API SW is an Islamic boarding school whose students are students and students; the data of students must be complete and should be superior to other boarding schools. This service is carried out using a PAR (Participation Action Research) approach. The method applied is through archiving management guidance activities to all administrators, providing excel training and contributing to the cottage office. And the implementation of service, the board of the API SW Islamic boarding school can arrange the administration well.